Surface structure of Gd₂₀Co₈₀ alloy - Kudin, V.G.; Rozouvan, S.G.; Staschuk, V.S. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2021)
Gd₂₀Co₈₀ alloy was studied applying experimental methods of spectral ellipsometry, atomic force, and scanning tunneling microscopy. The experimental results exhibit the eutectic two-phase structure of this alloy. Clusters of a phase with a lower content had a lesser concentration of free carriers, which resulted in smaller tunnel currents during the measurements. To analyze the experimental data, a theoretical approach was developed, which was based both on the quantum-mechanical methods of configurational interaction and on the three-diagonal Toeplitz matrices formalism. This approach allowed us to describe in detail the energy bands formation process in solid clusters with a relatively small quantity of atoms, which, as a consequence, enabled us to describe the Shockley surface states as well as the existence of a surface layer with partially formed energy bands. Spectral-ellipsometric measurements of Gd₂₀Co₈₀ alloy thin films confirmed a significant difference between the measured optical constants for 20-nm-thick films and larger films. Quantum-mechanical molecular calculus allowed us to obtain optical constants for several supercells of Gd-Co chemical compounds and confirmed the acquired experimental and theoretical results. Сплав Gd₂₀Co₈₀ досліджено за допомогою експериментальних методик спектральної еліпсометрії, атомно-силової та скануючої тунельної мікроскопії. Результати експериментів показали наявність евтектичної двофазної структури сплаву. Кластери фази з меншим питомим вмістом мали меншу концентрацію вільних носіїв, що призводило до менших значень тунельних струмів при вимірюваннях. Для аналізу експериментальних даних був розвинутий формалізм у рамках квантово-механічної методики конфігураційної взаємодії із застосуванням формалізму тридіагональних матриць Тепліца. Даний теоретичний підхід дозволив у деталях описати перехідний процес формування енергетичних зон у твердому тілі з порівняно невеликою кількістю атомів, що в тому числі, як один із наслідків, включає описання поверхневих станів Шоклі та поверхневого шару твердого тіла з неповністю сформованими енергетичними зонами. Спектрально-еліпсометричні вимірювання плівок сплаву Gd₂₀Co₈₀ підтвердили значну відмінність виміряних оптичних констант для плівок товщиною 20 нм та більш товстих плівок. Квантово-механічні чисельні розрахунки оптичних констант різних надкомірок хімічних сполук Gd-Co підтвердили отримані експериментальні та теоретичні результати.